Urbanonimy motywowane frazeologizmami jako forma gry onimicznej z pośrednikiem inicjacji czytelniczej w literaturze dziecięcej Agnieszki Zimnowodzkiej - IZABELA ŁUC (Stylistyka)
The article is aimed at exploring literary urbanonyms motivated by phraseologisms, derived from Humorki, a series of stories for children by Agnieszka Zimnowodzka. The categorical and formal properties of the bases used to create the described names require from the addressee appropriate communicative and cultural competences. Taking into account the age of the addressees of the stories, it was assumed that these formations may be semantically illegible for a child, so they were considered in the context of an onymic game with an adult reader – an intermediary in the reading initiation. The urbanonyms listed in the series of stories were described in terms of motivation and communication, with focus on their textual and semiotic structures, with the use of compiled research methods. The analysis of creations motivated by phraseological vocabulary proves that these names are not only a key link in the writer’s creative strategy, but also that – on each communication level – they have been subordinated to textual pragmatics. Names motivated by phraseologisms, apart from their primary functions – of localization and content, perform many other ones that interpenetrate the text – the illusive, humorous, informative, intertextual, creative, ludic, metatextual, cognitive, stylistic and evaluative functions.